2011
DOI: 10.1371/journal.pone.0018004
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Socio-Emotional Deficits in Platelet-Derived Growth Factor Receptor-β Gene Knockout Mice

Abstract: Platelet-derived growth factor (PDGF) is a potent mitogen. Extensive in vivo studies of PDGF and its receptor (PDGFR) genes have reported that PDGF plays an important role in embryogenesis and development of the central nervous system (CNS). Furthermore, PDGF and the β subunit of the PDGF receptor (PDGFR-β) have been reported to be associated with schizophrenia and autism. However, no study has reported on the effects of PDGF deletion on mice behavior. Here we generated novel mutant mice (PDGFR-β KO) in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 79 publications
1
46
2
Order By: Relevance
“…Contextual memory did not differ within the groups, even though the HGF and Plaur/HGF mice presented with nearly two-fold more PV + hippocampal interneurons. Previous studies have indicated that loss of PV + interneuron activity leads to impaired spatial memory [51, 52]. However, cued extinction was impaired in all the mutant genotypes, implying dysfunction of the MFC.…”
Section: Discussionmentioning
confidence: 81%
“…Contextual memory did not differ within the groups, even though the HGF and Plaur/HGF mice presented with nearly two-fold more PV + hippocampal interneurons. Previous studies have indicated that loss of PV + interneuron activity leads to impaired spatial memory [51, 52]. However, cued extinction was impaired in all the mutant genotypes, implying dysfunction of the MFC.…”
Section: Discussionmentioning
confidence: 81%
“…Interneurons expressing PV exhibit the fast-spiking phenotype and have been suggested to be involved in gamma oscillations [5,6]. Disruption of gamma oscillation has been suggested to underlie psychiatric disorders such as schizophrenia [57] and autism [58] and may be attributable to deficits in GABAergic PV-positive interneurons [57,59,60]. Furthermore, adverse prenatal or early life events such as exposure to ethanol and maternal separation alter emotional responsiveness and the number of PV-positive interneurons in BLA, medial septum, medial prefrontal cortex, and hippocampus [61-64].…”
Section: Discussionmentioning
confidence: 99%
“…8 Together, these findings suggest that TCDD affects the GABAergic neurons during brain development depending on gender. Because an altered GABAergic system and CaMKII activity have been observed in mouse models of ASD and individuals with schizophrenia suffer from social disturbances, [40][41][42][43] TCDD may increase autistic traits through the GABAergic system and CaMKII. Recently, perinatal TCDD exposure was reported to decrease the number of parvalbumin-immunoreactive neurons (putative inhibitory interneurons) in the limbic system, including the amygdala and hippocampus, in rats; 33 these findings suggest that alterations in the inhibitory interneurons in these brain regions partly mediate the effects of TCDD on higher brain functions.…”
Section: Validity Of Dioxin Effectsmentioning
confidence: 99%